2015
DOI: 10.3390/ma8095297
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation of Adsorption and Diffusion of Ions on Pristine, Defective and B-doped Graphene

Abstract: We performed first-principles calculations to reveal the possibility of applying pristine, defective, and B-doped graphene in feasible negative electrode materials of ion batteries. It is found that the barriers for ions are too high to diffuse through the original graphene, however the reduced barriers are obtained by introducing defects (single vacancy, double vacancy, Stone–Wales defect) in the graphene. Among the three types of defects, the systems with a double vacancy could provide the lowest barriers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…39,40 Heteroatom doping of graphene, including N, B, S, and P, has also been studied. 8,34,36,[41][42][43][44] N doping has shown to improve Na diffusion in bilayer graphene. 8,45 S and P doping could change the electronic character of carbon sheets, whereas B incorporation has shown to lead to a better thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Heteroatom doping of graphene, including N, B, S, and P, has also been studied. 8,34,36,[41][42][43][44] N doping has shown to improve Na diffusion in bilayer graphene. 8,45 S and P doping could change the electronic character of carbon sheets, whereas B incorporation has shown to lead to a better thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The eight membered rings are similar to a divacancy which has been found to increase Li capacity. 26,27,[29][30][31][32] membranes have also been the subject of several theoretical studies. [34][35][36][37][38][39] These have mainly focused on the electronic properties of the BP membranes and its ribbons and nanotubes where it was found that the pristine sheet is metallic with no band gap.…”
Section: Introductionmentioning
confidence: 99%
“…A 4 × 4 supercell with a periodic boundary condition along the x-y plane was employed for the infinite graphene sheet model. The vacuum was set with 20 Å in the z direction, which could avoid the interaction between periodic graphene layers [ 40 ]. By removing a chosen C atom in intrinsic graphene, the model of VG was built.…”
Section: Theoretical Methodsmentioning
confidence: 99%